PENGARUH ONLINE CUSTOMER REVIEW DAN RATING TERHADAP KEPUTUSAN PEMBELIAN DI LAZADA - Winda Ayu Sugiarto; Rifki Hanif (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Online Customer Reviews and Online Customer Ratings are very valuable features for consumers to obtain information for consideration in deciding to purchase online. This study aims to analyze the influence of Online Customer Reviews and Online Customer Ratings on Purchase Decisions on the Lazada E-commerce platform. This research was conducted using quantitative methods and associative approaches. The population in the study were 143 management students at the Asia Institute of Malang and the research sample was obtained using a purposive sampling technique with a total of 107 people. Data was collected through a survey using a questionnaire to students who made purchases through Lazada. The collected data were analyzed using multiple linear regression analysis to examine the relationship between Online Customer Reviews, Online Customer Ratings, and Purchase Decisions. The results of data analysis show that Online Customer Reviews have a positive and significant influence on Purchasing Decisions. Likewise, Online Customer Rating also has a positive and significant influence on Purchase Decision. In addition, the results of the F test show that simultaneously, Online Customer Reviews and Online Customer Ratings together influence Purchase Decisions Keywords: Reviews, Ratings, Purchasing Decisions